A theoretical framework for retrospective T2∗ correction to the arterial input function in quantitative myocardial perfusion MRI. Issue 2 (24th March 2021) - Fan, Lexiaozi; Allen, Bradley D.; Culver, Austin E.; Hsu, Li‐Yueh; Hong, Kyungpyo; Benefield, Brandon C.; Carr, James C.; Lee, Daniel C.; Kim, Daniel
Abstract : Purpose: To develop and evaluate a flexible, Bloch‐equation based framework for retrospective T 2 ∗ correction to the arterial input function (AIF) obtained with quantitative cardiac perfusion pulse sequences. Methods: Our framework initially calculates the gadolinium concentration [Gd] based on T1 measurements alone. Next, T 2 ∗ is estimated from this initial calculation of [Gd] while assuming fast water exchange and using the literature native T2 and static magnetic field variation (ΔB0 ) values. Finally, the [Gd] is recalculated after performing T 2 ∗ correction to the Bloch equation signal model. Using this approach, we performed T 2 ∗ correction to historical phantom and in vivo, dual‐imaging perfusion data sets from 3 different patient groups obtained using different pulse sequences and imaging parameters. Images were processed to quantify both the AIF and resting myocardial blood flow (MBF). We also performed a sensitivity analysis of our T 2 ∗ correction to ±20% variations in native T2 and ΔB0 . Results: Compared with the ground truth [Gd] of phantom, the normalized root‐means‐square‐error (NRMSE) in measured [Gd] was 5.1%, 1.3%, and 0.6% for uncorrected, our corrected, and Kellman's corrected, respectively. For in vivo data, both the peak AIF (7.0 ± 3.0 mM vs. 8.6 ± 7.1 mM, 7.2 ± 0.9 mM vs. 8.6 ± 1.7 mM, 7.7 ± 1.8 mM vs. 10.3 ± 5.1 mM, P < .001) and resting MBF (1.3 ± 0.1 mL/g/min vs. 1.1 ± 0.1 mL/g/min, 1.3 ± 0.1 mL/g/min vs. 1.1 ± 0.1 mL/g/min, 1.2 ± 0.1 mL/g/min vs. 0.9 ± 0.1 mL/g/min, P < .001) values were significantly different between uncorrected and corrected for all 3 patient groups. Both the peak AIF and resting MBF values varied by <5% over the said variations in native T2 and ΔB0 . Conclusion: Our theoretical framework enables retrospective T 2 ∗ correction to the AIF obtained with dual‐imaging, cardiac perfusion pulse sequences.